Pharmacology for Nurses : A Pathophysiologic Approach - Adams, Michael, 1951-; Holland, Leland Norman, 1957-; Urban, Carol Q. (Carol Quam) (Hoboken, NJ : Pearson, 2020)
"Pharmacology for Nurses: A Pathophysiologic Approach simplifies pharmacology by linking it tightly to therapeutic goals. Instead of learning about drugs in isolation, students approach them by body systems and diseases in order to draw connections between A&P, diseases, and drug interventions. Engaging features and exercises relate pharmacology to nursing care, while discussion of alternative therapies and cultural and lifespan considerations give further context for clinical decisions. The 6th edition adds the most current pharmacotherapeutics and advances in pathophysiology." -- Provided by publisher.
Unit 1: Core concepts in pharmacology -- Unit 2: Pharmacology and the nurse-patient relationship -- Unit 3: The nervous system -- Unit 4: The cardiovascular and urinary systems -- Unit 5: The immune system -- Unit 6: The respiratory system -- Unit 7: The gastrointestinal system -- Unit 8: The endocrine system -- Unit 9: The integumentary system, eyes, and ears.
Includes bibliographical references and index.
Keywords: Pharmacology; Nurses; Drug Therapy; Pharmacological Phenomena; Pharmacology; Nurses Instruction